Comparative Archaeologies
XVI, 852 p.
Keywords: Archaeology, as with all of the social sciences, has always been characterized by competing theoretical propositions based on diverse bodies of locally acquired data. In order to fulfill local, regional expectations, different goals have been assigned to the practitioners of Archaeology in different regions. These goals might be entrenched in local politics, or social expectations behind cultural heritage research. This comprehensive book explores regional archaeologies from a sociological perspective—to identify and explain regional differences in archaeological practice, as well as their existing similarities. This work covers not only the currently-dominant Anglo-American archaeological paradigm, but also Latin America, Western and Eastern Europe, Asia, and Africa, all of which have developed their own unique archaeological traditions. The contributions in this work cover these "alternative archaeologies," in the context of their own geographical, political, and socio-economic settings, as well as the context of the currently accepted mainstream approaches.